2017
DOI: 10.1007/s11259-017-9694-9
|View full text |Cite
|
Sign up to set email alerts
|

B-mode and Doppler ultrasound of chronic kidney disease in dogs and cats

Abstract: Ultrasound is the imaging test of choice for renal evaluation, because it provides information about the position, size, shape, internal architecture and hemodynamics of the kidneys without harming the patient. In chronic kidney disease, the main findings observed in B-mode ultrasound images are increased cortical echogenicity, loss of corticomedullary differentiation, reduced renal volume and irregular renal contour, and when these changes are associated, they are indicative of end-stage renal disease. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 30 publications
4
70
0
2
Order By: Relevance
“…The International Renal Interest Society (IRIS) stages of CKD are based on the evaluation of serum creatinine, symmetric dimethylarginine (SDMA), proteinuria, and blood pressure, in order to facilitate diagnosis, prognostic evaluation, and treatment of the disease [1,3]. Abdominal ultrasonography (US) is routinely performed and recommended in animals with renal disease, or when creatinine serum levels are increased [4][5][6]. Ultrasonography is the first imaging investigation required in both human and veterinary patients with chronic renal failure [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The International Renal Interest Society (IRIS) stages of CKD are based on the evaluation of serum creatinine, symmetric dimethylarginine (SDMA), proteinuria, and blood pressure, in order to facilitate diagnosis, prognostic evaluation, and treatment of the disease [1,3]. Abdominal ultrasonography (US) is routinely performed and recommended in animals with renal disease, or when creatinine serum levels are increased [4][5][6]. Ultrasonography is the first imaging investigation required in both human and veterinary patients with chronic renal failure [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the advanced diagnostic imaging techniques, particularly renal ultrasonographic shear-wave elastography (SWE), have been increasingly performed in humans [ 36 , 37 ]. Increases of both cortical and medullary renal echogenicity detected by B-mode ultrasound are related to the CKD lesions [ 38 ]; these increases may also be present in dogs without evidence of renal impairment [ 39 ]. SWE can evaluate renal parenchyma elasticity or renal tissue stiffness [ 40 , 41 ] by facilitating the Young’s modulus (E) value measurements [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although different RI intervals are specified one by one, the RI value is considered abnormal when it exceeds 0.70 (Novellas et al, 2008 ;Mitchell et al, 1998;Morrow et al, 1996). RI and PI above the upper limit indicate the presence of renal disease (Bragato et al, 2017). The mean intrarenal RI value of healthy dogs was 0.54 ± 0.01 in our study.…”
Section: Resultsmentioning
confidence: 63%
“…As the first changes in renal diseases begin with the change in blood flow, renal Doppler ultrasonography, which is rarely used in veterinary practice is one of the most important diagnostic tools (Bragato et al, 2017). Previous studies have shown many normal RI values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation